The Impact of Foreign Direct Investment on New Firm Survival in the UK: Evidence for Static v. Dynamic Industries - Burke, Andrew; Gorg, H; Hanley, A (Springer Science Business Media, 2008)
The paper examines the impact of Foreign Direct Investment (FDI) on the survival of business start-ups. FDI has potential for both negative displacement/ competition effects as well as positive knowledge spillover and linkage effects on new ventures. We find a net positive effect for the whole dataset. However, a major contribution of the paper is to outline and test an argument that this effect is likely to be comprised of a net negative effect in dynamic industries (high churn: firm entry plus exit relative to the stock of firms) alongside a net positive effect in static (low churn) industries. We find evidence to support this view. The results identify new effects of globalisation on enterprise development with associated challenges for industrial policy.
Keywords: New Firms; Foreign direct Investment; Dynamic industries; FDI